(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Deep ecology emphasizes the interconnectedness and intrinsic value of all living beings and the Earth’s ecosystem. These two perspectives provide valuable lenses through which to analyze Ramanujan’s poetic works. Deep ecology recognizes the inherent worth of non-living entities and promotes ecological harmony and sustainability. It advocates for moving away from a mindset of dominance over nature and towards one of respect and humility. Interconnectedness of all living beings, the intrinsic value of non-human life, and the need for ecological awareness and responsible stewardship is discussed in this paper. Further this study explores that deep ecology is a movement focused on environmental awareness. Unlike human-centered approaches, deep ecology is ecocentric, meaning it prioritizes nature over human interests. It views pollution not only as a crime against humanity but as a crime against all life. The destructive actions of humans have caused severe harm to the environment, leading to issues like ozone depletion, water pollution, and global warming. This is why deep ecology is important. It emphasizes that environmental ethics are essential for addressing the growing environmental crises caused by human activities. This paper argues that Ramanujan’s poetic voice contributes meaningfully ecocritical discourse by encouraging ecological awareness and environmental responsibility. His poetry is like a medium through which ecological values can be both expressed and internalized within a broader movement toward environmental ethics in literature. Ultimately, this study affirms that Ramanujan’s poetry embodies the spirit of deep ecology, offering a poetic model for rethinking humanity’s place within the natural world and inspiring a more sustainable and compassionate environmental ethos. . By analyzing poems such as ‘The Striders’, ‘Looking for a Cousin on a Swing’ this study highlights on a sense of respect and harmony with nature which is central tenet of deep ecology.